Black Voice Portrayed in The Movie of The Hidden Figures by Theodore Melfi - Puspita, Maya; Ramdhani, Muhammad Iqbal (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The film Hidden Figures is based on the actual tale of three African-American women who work at NASA on space rocket launches. Katherine G. Johnson, Mary Jackson, and Dorothy Vaughan are the three African-American women. With the backdrop of the 1960s, these three women face the discrimination (differences in race or skin color) in their workplace at NASA. This study aims to explore the theory of black feminism from Patricia Hill Collins and integrate it with the Self Defenses Mechanism theory from Sigmund Freud about how they faced problems at that time. This research using a qualitative descriptive approach. This study finds black feminism in the film Hidden Figures in the form of discrimination experienced by these characters in the form of gender, race and class. However, the resistance carried out by these characters is through Aggression, namely expressing anger, Apathetic, namely by withdrawing not to enter into a problem, Isolation, namely respecting something that causes frustration, and finally, Introjection, which is taking the positive side of other people.Â